THE EFFECT OF EXTRACORPOREAL SHOCK WAVE THERAPY IN TREATMENT OF CALCIFYING TENDINITIS OF THE ROTATOR CUFF OF THE SHOULDER - Manoleva, Maja; Koevska, Valentina; Mitrevska, Biljana; Gocevska, Marija; Savevska, Cvetanka Gjerakaroska; Ivanovska, Biljana Kalchovska; Nikolovska, Liljana Malinovska (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
Calcifying tendinitis of a shoulder is a frequent disorder with an unknown etiology. It is usually treated with different physical therapy modalities where extracorporeal shockwave therapy comes as a new effective method. Objective: to assess the impact of extracorporeal shockwave therapy in the treatment of calcifying tendinitis of the rotator cuff of the shoulder. The study is a prospective, monocentric clinical study involving 13 patients who received extracorporeal shockwave therapy in 5 treatments, applied once a week in one session. The patients were evaluated with a Visual analog scale for pain and measurement of the range of motion of the shoulder joint. Clinical findings were evaluated before starting the treatment with extracorporeal shockwave therapy and at the end of the treatment, 5 weeks later. After the treatment all the patients had statistically significantly better results in the Visual analogue scale for pain and the range of motion in the shoulder joint. Extracorporeal shock wave therapy is a safe and non-invasive treatment that reduces pain and improves range of motion in the treatment of calcifying tendinitis of the rotator cuff. Keywords : calcifying tendinitis, shoulder, extracorporeal shock wave therapy. https://doi.org/10.55302/JMS2251163m